Legal Review of Corporate Crime Against Sanctions as Substitute for Fines (District Court of Serang, Banten, Indonesia) - Reine Rofiana (Nurani Hukum, 2022)
This study aims to examine, analyze and understand the concept of corporate criminal responsibility and the reformulation of alternative criminal penalties against corporations for unpaid fines. Several criminal cases that have been resolved at the Serang District Court until 2020 have not found a single corporation that has been tried and convicted for committing a corporate crime. The judge is only passive, the judge's authority is only to examine, hear and decide cases based on the indictment made by the public prosecutor. Return of court case files to the prosecutor's office only if the indictment does not meet material requirements. PERMA Number 13 of 2016 does not regulate if the criminal fine cannot be paid by the corporation due to insufficient or non-existent corporate assets. This research was conducted in a normative juridical manner so that the disclosure was bound by a method based on the requirements of deductive logic, prioritizing literature studies with secondary data bases, namely primary, secondary and tertiary legal materials. In terms of evidence in court, if the fact is found that the corporation should also be a legal subject who can be held criminally responsible, the public prosecutor should have made a separate indictment for the legal subject of the corporation so that the corporation does not escape its responsibility. The provisions in PERMA No. 13 of the Year should regulate corporate assets if they do not pay the fines enough or even do not have the assets to pay the fines. Law enforcement officials should investigate the assets of the corporation first.